IDENTIFIKASI NILAI PENTING CAGAR BUDAYA PADA ISTANA DALAM LOKA, SUMBAWA - Alifah, Tsary Nabilah; Ginanjar, Agi (Multikultura, 2025)
Istana Dalam Loka, located in Sumbawa, is one of the cultural heritage assets in Sumbawa Regency that has not yet been officially designated as a cultural heritage site. Built in 1885, Istana Dalam Loka is a wooden palace that once served as the administrative center of the Sumbawa Sultanate as well as the residence of the king and his family. The palace stands as a historical witness containing numerous cultural and historical values, and therefore should be designated and protected in accordance with the Cultural Heritage Law. This study aims to identify the significant values possessed by Istana Dalam Loka and to assess its physical condition as part of efforts toward its protection and preservation. This research employs a qualitative method with descriptive analysis. The findings indicate that Istana Dalam Loka qualifies to be designated as a cultural heritage site because it holds important values in accordance with Law No. 11 of 2010. These include historical significance, particularly in political history, scientific significance for its research potential, as well as educational, religious, and cultural importance. The results of this study provide recommendations for the process of designation and grading of Istana Dalam Loka, Sumbawa, as an official cultural heritage site.